LITERATURE REVIEW: ANALISIS INTEGRASI CHATBOT DENGAN ELEMEN GAME UNTUK MENINGKATKAN ENGAGEMENT PENGGUNA DI PENDIDIKAN, BISNIS, DAN HIBURAN - Alifia Ardita; Ariel Chavya Ikhrima; Rika Wati (Jurnal Riset Sistem Informasi, 2026)
The integration of chatbots and gamification has increasingly been adopted as a strategy to create more interactive digital experiences. Chatbots and gamification function as motivational tools that enhance user engagement, and their application has expanded across various sectors of daily life. However, further understanding and research are still required to examine how the combination of these two approaches can produce optimal outcomes. This study aims to address two main research questions: how chatbots and gamification can complement each other in creating engaging user experiences, and in which contexts this integration produces the most significant impact. This research employs a Systematic Literature Review approach using the Grounded Theory Literature Review method. Articles were collected from Google Scholar and Garuda, with search criteria focusing on the use of chatbots integrated with gamification elements in the fields of education, business, and entertainment. The selection process involved screening titles, abstracts, publication years, and contextual relevance to ensure that only pertinent studies were analyzed further.The findings indicate that the integration of chatbots and gamification can strengthen interaction, increase motivation, and create more adaptive experiences across various contexts. In education, this combination provides more personalized learning support. In business settings, it enhances emotional connections with users, while in the entertainment sector, it creates more immersive experiences. Overall, this study confirms that the integration of these two technologies holds significant potential to enhance user engagement, although challenges remain in terms of design and the sustainability of their implementation.